Job Design and Work Performance: A Study of Health Care Personnel in Tripoli Medical Centre (TMC) - Zeyad Mohamed, Otman (2009)
The main purpose of this study was to determine the relationships between job design and work performance among 156 randomly selected healthcare personnel in Tripoli Medical Centre, Libya. The study also examined statistically significant differences in the respondents' work performance when grouped by gender, age, marital status, tenure, number of years working in the current hospital, number of years working in other hospitals, and place of residence. In assessing job design, the Multimethod Job Design Questionnaire (Cronbach Alpha=0.9064) developed by Campion (1988) was adopted, pilot-tested, and used in the research. In describing work performance, job evaluation records from the Human Resource Office in Tripoli Medical Centre were taken for the purpose of this study. Statistical tools used were frequency counts, percentages, means, t-test, One-Way ANOVA, Pearson's r, and Multiple Regression Analysis. Analyses were set at 0.05 level of significance using the SPSS (Version 14.0) computer software. Overall, the respondents "agreed" on the job design in the hospital. Across the sub-dimensions of job design, the respondents "agreed" on Motivational Approach, Biological Approach, and Perceptual-Motor Approach. However, respondents were "not sure" on Mechanistic Approach. The respondents experienced "high" level of work performance. There were statistically significant differences between work performance and (a) age, (b) marital status, (c) tenure, (d) number of years working in the current hospital, and(e) number of years working in other hospitals.